Validity and Practicality of Student Worksheet Based on Augmented Reality Applications of Mangrove Roots to Improve The Level of Spatial Thinking - Afnan, Muhammad Zahrudin; Puspitawati, Rinie Pratiwi (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2024)
The use of AR itself has entertaining elements that can increase students' interest in learning and playing, as well as real-world projections that involve the interaction of all five senses of students with technology, learning media with AR is very helpful in enhancing the learning process and students' interest in learning. such ARs. This is due to the fact that AR possesses traits and capabilities that are essentially identical to those of learning media, including functioning to convey knowledge exchanged between senders and recipients, or between teachers and students, can clarify how knowledge is delivered during the learning process and can stimulate interest and motivation learning.The purpose of this study is to produce Mangrove Root Augmented Reality application media as an innovative and practical learning media to improve students' spatial thinking skills in terms of the aspects of validity, practicality, and effectiveness which are named MANGROVIA application media. This type of research uses the ADDIE development model (analysis, Design, Development, Implementation, and Evaluation) with a pretest and posttest research design conducted by 30 students of class XI SMA. The details of the research results that have been carried out include the validity of the Augmented Reality application of Mangrove Roots getting an average percentage of 100%, the practicality of the Augmented Reality. Keywords: Spatial, Augmented Reality, Mangrove Roots